2019
DOI: 10.1016/j.jceh.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Bacterial Overgrowth in Patients With Cirrhosis

Abstract: Small intestinal bacterial overgrowth (SIBO) is defined by increased density and/or abnormal composition of microbiota in the small bowel. SIBO is often encountered in patients with cirrhosis as a result of impaired intestinal motility and delayed transit time, both of which are exacerbated by more severe liver disease. Additional risk factors for SIBO commonly encountered in cirrhotic patients include coexisting diabetes, autonomic neuropathy, and/or alcoholic use. Diagnosis of SIBO is performed by breath tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 75 publications
0
36
0
8
Order By: Relevance
“…The curative effect of rifaximin on improving the dietary intake may be due in part to the improvement of hepatic encephalopathy and small intestinal bacterial overgrowth (SIBO). Patients with hepatic encephalopathy have a high prevalence of SIBO and are often encountered with cirrhosis as a result of an impaired intestinal motility and delayed transit time, including malabsorption ( 23 ). Rifaximin is the best studied antibiotic for SIBO treatment, as it is a poorly absorbed oral antibiotic, which allows for local enteric antibacterial activity with a minimal risk of systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The curative effect of rifaximin on improving the dietary intake may be due in part to the improvement of hepatic encephalopathy and small intestinal bacterial overgrowth (SIBO). Patients with hepatic encephalopathy have a high prevalence of SIBO and are often encountered with cirrhosis as a result of an impaired intestinal motility and delayed transit time, including malabsorption ( 23 ). Rifaximin is the best studied antibiotic for SIBO treatment, as it is a poorly absorbed oral antibiotic, which allows for local enteric antibacterial activity with a minimal risk of systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in patients with cirrhosis, a reduced intestinal motility has been described. As a matter of fact, the consequent delayed small intestinal transit could represent a risk factor for dysbiosis [ 77 ].…”
Section: Behavioural Correlates Of Gut Dysbiosismentioning
confidence: 99%
“…For patients with liver cirrhosis, bacterial translocation (BT) as a result of intestinal gram-negative Enterobacteriaceae infections is the main cause of SBP occurrence and development [ 6 , 52 , 53 ]. Previous studies have shown that gastrointestinal stasis due to portal hypertension in patients with liver cirrhosis, intestinal bacterial overgrowth due to low levels of bile acid and gastric acid, delayed intestinal transport, altered intestinal permeability, and immune dysfunction promote BT and ultimately SBP [ 5 , 7 , 8 ] ( Figure 1 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…In recent studies, gastrointestinal stasis due to portal hypertension, relative lack of bile and gastric acid secretion, intestinal dyskinesia, and long-term use of broad-spectrum antibiotics in patients with liver cirrhosis are implicated in increased intestinal aerobic bacteria and colonic bacterial migration to the jejunum and duodenum. These changes further cause SIBO and promote BT, which is implicated in SBP prognosis in patients with liver cirrhosis [ 7 ]. Notably, the most common pathogenic microorganisms were isolated from the intestinal flora of cirrhotic ascites in SBP patients [ 69 ].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation